Lithium manganese iron phosphate material as well as preparation method and application thereof
By using ball milling and spray drying processes in the preparation of lithium manganese phosphate materials, carbon-coated lithium manganese phosphate materials with porous microsphere structures is solved, and the problems of low material stacking density, small conductivity and low specific energy are achieved, achieving the goal of high performance and simplification of the process.
Patent Information
- Application Number
- CN202411832476.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The low bulk density, low conductivity and low specific energy of lithium manganese phosphate materials, as well as complex processes, limit their commercial applications.
By mixing manganese source, iron source, phosphorus source with a water ball mill, adding lithium source, pyrophosphate and sucrose ball mill to form a high-stability slurry. The composite precursor of the microsphere structure was obtained by spray-drying treatment, and then calcined under an inert gas atmosphere to prepare a carbon-coated lithium manganese iron phosphate material with a porous microsphere structure.
The bulk density, conductivity and energy density of lithium manganese iron phosphate materials are improved, the process flow is simplified, suitable for large-scale production, and the circulation performance and magnification capabilities of the materials are improved.
Smart Images

Figure CN119706777A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium manganese iron phosphate material and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery is a kind of energy storage device widely used in energy storage field, power battery and portable electronic devices. Lithium-ion battery has advantages such as high working voltage, low self-discharge and good safety. Lithium-ion battery is mainly composed of positive electrode material, negative electrode material, electrolyte, diaphragm and shell, among which the positive electrode materials mainly include lithium cobalt oxide, lithium manganese oxide, nickel manganese binary system, nickel cobalt manganese ternary system, nickel cobalt aluminum ternary system and lithium iron phosphate. Olivine-type phosphate positive electrode materials represented by lithium iron phosphate (LiMPO4, M=Fe, Co, Ni and Mn) have excellent thermal stability and chemical stability, are environmentally friendly, non-toxic, have good cycle performance and low raw material price, and have excellent charge and discharge platform. Lithium iron phosphate has an olivine structure and is a Pbnm orthorhombic space group. The stable PO bond in the LiFePO4 unit can inhibit the generation of O2 during charge and discharge, and inhibit the dissolution of the material matrix by the electrolyte, and has excellent safety performance. One disadvantage of lithium iron phosphate material is that its voltage platform is relatively low, only 3.4V (relative to Li + / Li), so although its theoretical specific capacity (170mAh / g) and actual specific capacity (150mAh / g) are high, its energy density is average. Lithium manganese phosphate (LiMnPO4) is an olivine structure cathode material with similar properties to lithium iron phosphate. In addition to having the same advantages as lithium iron phosphate in terms of thermal stability and chemical stability, LiMnPO4 has a voltage platform (4.1V, relative to Li + / Li) is higher than that of lithium iron phosphate, and its theoretical specific capacity is close to that of lithium iron phosphate. Its theoretical energy density is about 20% higher than that of lithium iron phosphate. However, the conductivity of lithium manganese phosphate (<10 -12 S / m) and lithium ion conductivity (<10 -19 m 2 / s) is worse than lithium iron phosphate and is at the insulator level, which seriously affects its application.
[0003] Lithium iron manganese phosphate (LiMn 1-x Fe xPO4, LMFP) is a solid solution material composed of lithium iron phosphate and lithium manganese phosphate. It has similar properties to lithium iron phosphate and lithium manganese phosphate, and has good thermal stability and chemical stability. At the same time, its operating voltage and energy density are improved compared with lithium iron phosphate, and its conductivity and lithium ion conductivity are improved compared with lithium manganese phosphate. It is a positive electrode material that deserves great attention. Among the many preparation processes of lithium iron manganese phosphate materials, the solid phase method is widely used in the preparation of lithium iron manganese phosphate positive electrode materials because of its advantages such as simple process, less equipment required, easy production, and low cost. First, a uniform iron manganese precursor is synthesized, such as ferrous manganese oxalate, ferrous manganese phosphate, ferrous manganese phosphate, ferric manganese oxide, etc., and then it is mixed with lithium carbonate and a carbon source and calcined to prepare lithium iron manganese phosphate materials. There are many studies, but the difficulty of this preparation method lies in the synthesis of a uniform iron manganese precursor and the complex process flow. In addition, due to certain defects in the material itself, such as low ion conductivity, low specific energy, and small primary particle size, LiMn 1-x Fe x The stacking density of PO4 electrode materials is reduced, and the specific capacity, rate performance and cycle performance are difficult to meet the requirements of practical applications, which restricts the commercial application process of lithium manganese iron phosphate materials. It is urgent to develop a method suitable for producing high-performance lithium manganese iron phosphate materials. Summary of the invention
[0004] The main purpose of the present invention is to provide a lithium iron manganese phosphate material and a preparation method and application thereof, so as to solve the problems of low packing density, low conductivity, low specific energy and complex process of the lithium iron manganese phosphate material in the prior art.
[0005] In order to achieve the above object, one aspect of the present invention provides a method for preparing a lithium manganese iron phosphate material, comprising the following steps:
[0006] Step S1, mixing a manganese source, an iron source, a phosphorus source and water by ball milling to obtain a first mixed slurry;
[0007] Step S2, ball-milling the lithium source, pyrophosphate, sucrose and the first mixed slurry to obtain a second mixed slurry;
[0008] Step S3, spray drying the second mixed slurry to obtain a composite precursor with a microsphere structure;
[0009] Step S4: calcining the composite precursor of the microsphere structure at a calcination temperature of 520-700° C. in an inert gas atmosphere to obtain lithium manganese iron phosphate material.
[0010] Furthermore, the molar ratio of manganese in the manganese source, iron in the iron source, phosphorus in the phosphorus source and lithium in the lithium source is (0.5-0.8):(0.2-0.5):1:(0.8-1.2), preferably ((0.5-0.8):(0.2-0.5):1:(0.9-1.1).
[0011] Furthermore, based on the sum of the weights of the manganese source, the iron source, the phosphorus source, the lithium source, the pyrophosphate and the sucrose being 100%, the mass of the sucrose is 3%-7%.
[0012] Furthermore, based on the sum of the weights of the manganese source, the iron source, the phosphorus source, the lithium source, the pyrophosphoric acid and the sucrose being 100%, the mass of the pyrophosphoric acid is 0.5%-2%.
[0013] Furthermore, based on the sum of the weights of the manganese source, the iron source, the phosphorus source, the lithium source, the pyrophosphate and the sucrose as 100%, the mass of water is 80% to 300%, preferably 90% to 120%.
[0014] Further, the manganese source is selected from manganese carbonate 、 One or more of manganese acetate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese nitrate, manganese tetraoxide, manganese trioxide or manganese dioxide.
[0015] Furthermore, the iron source is selected from one or more of ferrous acetate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferrous oxide, ferrous sulfate, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, ferrosoferric oxide, ferrous phosphate or ferrous phosphate.
[0016] Furthermore, the phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate, ammonium phosphate, phosphorus pentoxide, phosphorous acid, and diammonium hydrogen phosphate.
[0017] Furthermore, the lithium source is selected from one or more of lithium carbonate, lithium bicarbonate, lithium acetate, lithium formate, lithium citrate, lithium chloride, lithium bromide, lithium hydroxide, lithium tert-butoxide, lithium benzoate, lithium phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, lithium oxalate or lithium sulfate.
[0018] Furthermore, in step S4, the calcination time is 4-8 hours, preferably 6 hours.
[0019] Preferably, in step S4, the calcination temperature is 580-650°C.
[0020] Preferably, in step S4, the composite precursor of the microsphere structure is heated to the calcination temperature at a heating rate of 3-7° C. / min under an inert gas atmosphere.
[0021] Further, in step S1, a manganese source, an iron source and a phosphorus source are first mixed to obtain a mixture, and the mixture is dispersed with deionized water and then ball milled.
[0022] Preferably, in step S1, the ball milling time is 350-450 rpm, and the ball milling time is 2-8 h.
[0023] Preferably, in step S2, the ball milling time is 350-450 rpm, and the ball milling time is 2-8 h.
[0024] Preferably, during the spray drying process, the feed peristaltic pump frequency is 5-40 Hz and the temperature is 100-110°C.
[0025] According to another aspect of the present invention, a lithium iron manganese phosphate material is provided, which is prepared according to the above method for preparing the lithium iron manganese phosphate material. The lithium iron manganese phosphate material has a porous microsphere structure, and the porous microspheres are formed by aggregation of nano primary particles. The nano primary particles include lithium iron manganese phosphate nanoparticles and a carbon layer coated on the surface of the lithium iron manganese phosphate nanoparticles.
[0026] Furthermore, the particle size of the porous microspheres is 10-20 microns.
[0027] Furthermore, the particle size of the nano primary particles is 50-100 nm.
[0028] Furthermore, the thickness of the carbon layer is 2-5 nm.
[0029] Furthermore, the material composition formula of lithium manganese iron phosphate nanoparticles is LiMn 1-x Fe x PO4, where 0.2≤x≤0.5.
[0030] Furthermore, the specific surface area of lithium manganese iron phosphate material is 20-25m 2 g -1 .
[0031] Furthermore, the tap density of the lithium manganese iron phosphate material is 1-1.5 g / cm 3 .
[0032] According to another aspect of the present invention, there is provided a lithium iron manganese phosphate composite material, comprising the lithium iron manganese phosphate material as described above.
[0033] According to another aspect of the present invention, a positive electrode plate is provided, the positive electrode plate comprising the above lithium manganese iron phosphate material.
[0034] According to another aspect of the present invention, there is provided a lithium-ion battery comprising the above positive electrode plate.
[0035] By applying the technical solution of the present invention, a first mixed slurry is obtained by mixing a manganese source, an iron source, a phosphorus source and water by ball milling, and then a lithium source, pyrophosphoric acid and sucrose are added and ball milled to form a highly stable slurry. A composite precursor with a microsphere structure is obtained by spray drying. Sucrose is used as a carbon source. Combined with the optimization of the sintering temperature and the addition of pyrophosphoric acid to optimize the microsphere structure during the calcination process, a carbon-coated lithium manganese iron phosphate material with a porous microsphere structure is obtained by calcination. On the one hand, the surface of the prepared lithium iron manganese phosphate is coated with a carbon layer, which is beneficial to improving the electron conduction in the lithium iron manganese phosphate particles and preventing the lithium iron manganese phosphate particles from being corroded by the electrolyte, so that it has good cycle performance; on the other hand, the prepared lithium iron manganese phosphate material is a micron-sized spherical powder, which can be more densely stacked, which is helpful to improve the tap density of the material and improve the energy density; in addition, the porous microsphere structure of the material has a large specific surface area, which makes the material easy to contact the electrolyte and can be effectively used for lithium storage, and the high porosity and high conductivity of the porous microsphere structure will promote the transmission of lithium ions and electrons, thus showing a high rate capability. When the current density returns to a low rate, the reversible capacity is quickly restored, showing the strong tolerance of the material to the rapid insertion / extraction of lithium ions; furthermore, the high-stability slurry is sprayed to form a composite precursor with uniform distribution of Mn, Fe, P and O elements, and is further calcined to generate microsphere particles with uniform distribution of Mn, Fe, P and O elements, which is beneficial to improve the ion transmission rate, rate performance, gram capacity and cycle reversibility of the battery material. Finally, the above method can obtain a carbon-coated lithium manganese iron phosphate material with a porous microsphere structure after two mixing and one calcination. The process is simple and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0037] Figure 1 The XRD pattern of the lithium iron manganese phosphate material prepared in Example 1;
[0038] Figure 2 (a) SEM image of micron-sized secondary particles, (b) SEM image of nano-sized primary particles, and (c) EDX elemental imaging of Mn, Fe, P, and O elements in the micron-sized secondary particles of the lithium manganese iron phosphate material prepared in Example 1;
[0039] Figure 3 HR-TEM image of nano-scale primary particles in the lithium manganese iron phosphate material prepared in Example 1;
[0040] Figure 4 This is a graph showing the capacity retention rate of the battery prepared in Example 1 after 200 cycles at 1C. DETAILED DESCRIPTION
[0041] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0042] As described in the background technology, the prior art lithium iron manganese phosphate material has the problems of low bulk density, low conductivity, low energy density and complex process. In order to solve the above problems, the present invention provides a preparation method of lithium iron manganese phosphate material, comprising the following steps: step S1, mixing a manganese source, an iron source, a phosphorus source and water by ball milling to obtain a first mixed slurry; step S2, ball milling a lithium source, pyrophosphoric acid, sucrose and the first mixed slurry to obtain a second mixed slurry; step S3, spray drying the second mixed slurry to obtain a composite precursor of a microsphere structure; step S4, calcining the composite precursor of the microsphere structure at a calcination temperature of 520-700°C in an inert gas atmosphere to obtain the lithium iron manganese phosphate material.
[0043] The preparation method of the lithium iron manganese phosphate material based on the technical solution of the present invention is to obtain a first mixed slurry by mixing a manganese source, an iron source, a phosphorus source and water by ball milling, and then add a lithium source, pyrophosphoric acid and sucrose to form a high-stability slurry by ball milling, and obtain a composite precursor with a microsphere structure by spray drying. Sucrose is used as a carbon source, combined with the optimization of the sintering temperature and the optimization of the microsphere structure by adding pyrophosphoric acid during the calcination process, and a carbon-coated lithium iron manganese phosphate material with a porous microsphere structure is obtained by calcination. On the one hand, the surface of the prepared lithium iron manganese phosphate is coated with a carbon layer, which is beneficial to improving the electron conduction in the lithium iron manganese phosphate particles and preventing the lithium iron manganese phosphate particles from being corroded by the electrolyte, so that it has good cycle performance; on the other hand, the prepared lithium iron manganese phosphate material is a micron-sized spherical powder, which can be more densely stacked, which is helpful to improve the tap density of the material and improve the energy density; in addition, the porous microsphere structure of the material has a large specific surface area, which makes the material easy to contact the electrolyte and can be effectively used for lithium storage, and the high porosity and high conductivity of the porous microsphere structure will promote the transmission of lithium ions and electrons, thus showing a high rate capability. When the current density returns to a low rate, the reversible capacity is quickly restored, showing the strong tolerance of the material to the rapid insertion / extraction of lithium ions; furthermore, the high-stability slurry is sprayed to form a composite precursor with uniform distribution of Mn, Fe, P and O elements, and is further calcined to generate microsphere particles with uniform distribution of Mn, Fe, P and O elements, which is beneficial to improve the ion transmission rate, rate performance, gram capacity and cycle reversibility of the battery material. Finally, the above method can obtain a carbon-coated lithium manganese iron phosphate material with a porous microsphere structure after two mixing and one calcination. The process is simple and suitable for large-scale production.
[0044] Based on obtaining high-performance lithium iron manganese phosphate material, in some embodiments, the molar ratio of manganese element in the manganese source, iron element in the iron source, phosphorus element in the phosphorus source and lithium element in the lithium source is (0.5-0.8): (0.2-0.5): 1: (0.8-1.2), preferably (0.5-0.8): (0.2-0.5): 1: (0.9-1.1), so as to obtain high yield and high purity LiMn 1-x Fe x PO4.
[0045] In some embodiments, the sum of the weights of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose is 100%, and the mass of sucrose is 3%-7%. Sucrose is used as a carbon source, and the optimization of its addition amount and the control of the sintering temperature are beneficial to prevent the excessive growth of nano primary particles and the large aggregation of primary particles. Sucrose, as a natural carbon source, will form a more uniform continuous carbon layer during the thermal decomposition process. Under this addition amount, a more uniform carbon coating layer and a regular porous microsphere structure can be obtained.
[0046] In some embodiments, the mass of pyrophosphoric acid is 0.5%-2%, based on the sum of the weight of manganese source, iron source, phosphorus source, lithium source, pyrophosphoric acid and sucrose as 100%. The addition of pyrophosphoric acid can improve the crystallinity of lithium iron manganese phosphate, affect the microstructure of the final product, including particle size, shape and element distribution, thereby affecting the performance of lithium iron manganese phosphate as a battery material, and pyrophosphoric acid can promote the pyrolysis of carbon source (such as sucrose) during calcination, which is conducive to the formation of a uniform carbon coating layer. With this addition amount, a more uniform and regular porous microsphere structure and a uniform carbon coating layer can be obtained.
[0047] In some embodiments, based on the sum of the weights of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose as 100%, the mass of water is 80% to 300%, which is conducive to obtaining a stable slurry system for spray drying and obtaining a higher drying efficiency. The mass of water is preferably 90% to 120%.
[0048] In one embodiment, the manganese source is selected from one or more of manganese carbonate, manganese acetate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese nitrate, manganese tetraoxide, manganese trioxide or manganese dioxide.
[0049] In one embodiment, the iron source is selected from one or more of ferrous acetate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferrous oxide, ferrous sulfate, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, ferric oxide, ferrous phosphate or ferrous phosphate.
[0050] In one embodiment, the phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, phosphorous acid, and diammonium hydrogen phosphate.
[0051] In one embodiment, the lithium source is selected from one or more of lithium carbonate, lithium bicarbonate, lithium acetate, lithium formate, lithium citrate, lithium chloride, lithium bromide, lithium hydroxide, lithium tert-butoxide, lithium benzoate, lithium phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, lithium oxalate or lithium sulfate.
[0052] In a preferred embodiment, in step S4, the calcination time is 4-8h. The temperature and time during the calcination process affect the carbon structure and the coating effect, and the calcination temperature also affects the degree of primary particle agglomeration and the growth rate of the primary particles. In addition, pyrophosphoric acid can be used as a flux to lower the melting point of the entire system, making the raw materials easier to melt and mix, thereby facilitating the formation of lithium manganese iron phosphate particles with uniform distribution of each element within the above time. The above calcination time is conducive to obtaining a regular, highly dispersed porous microsphere structure with uniform distribution of Mn, Fe, P and O elements and a uniform, continuous carbon coating layer with good electrical conductivity; The preferred calcination time is 6 hours in order to form a regular porous microsphere structure with suitable particle size and high crystallinity and reduce energy consumption; the preferred calcination temperature is 580-650°C, which is easy to obtain a uniform and continuous conductive carbon layer, and reduce excessive agglomeration of primary particles and excessive growth of primary particles, so as to obtain a more regular porous microsphere structure and obtain a lithium manganese iron phosphate material with higher porosity, high conductivity and high tap density; the composite precursor of the microsphere structure is preferably heated to the calcination temperature at a heating rate of 3-7°C / min in an inert gas atmosphere to obtain a porous microsphere structure with more regular morphology and high particle crystallinity.
[0053] In order to improve the dispersion effect of the first mixed slurry, in some embodiments, in step S1, the manganese source, the iron source and the phosphorus source are first mixed to obtain a mixture, and the mixture is dispersed with deionized water and then ball-milled; in order to fully disperse the manganese source, the iron source and the phosphorus source, in step S1, the ball milling time is 350-450rpm, and the ball milling time is 2-8h; in order to obtain a second mixed slurry with high stability, it is preferred that in step S2, the ball milling time is 350-450rpm, and the ball milling time is 2-8h.
[0054] According to another aspect of the present invention, a lithium iron manganese phosphate material is provided, which is prepared according to the above method for preparing the lithium iron manganese phosphate material. The lithium iron manganese phosphate material has a porous microsphere structure, and the porous microspheres are formed by aggregation of nano primary particles. The nano primary particles include lithium iron manganese phosphate nanoparticles and a carbon layer coated on the surface of the lithium iron manganese phosphate nanoparticles.
[0055] In some embodiments, the porous microspheres have a particle size of 10-20 microns to obtain a higher packing density and a high energy density.
[0056] In some embodiments, the particle size of the nano primary particles is 50-100nm. The above-mentioned smaller primary crystal particle size can improve the conductivity of the material, while shortening the distance between the pores. The interconnected three-dimensional pore channels are conducive to shortening the deintercalation distance of lithium ions. The material has a higher rate performance, and the lithium manganese iron phosphate material has a porous microsphere structure and the above-mentioned primary particle size, so that it has both high energy density and battery performance.
[0057] In some embodiments, the thickness of the carbon layer is 2-5 nm to obtain better electrical conductivity.
[0058] In some embodiments, the material composition of lithium manganese iron phosphate nanoparticles is generally LiMn 1-x Fe x PO4, wherein 0.2≤x≤0.5, so as to obtain lithium manganese iron phosphate having both high capacity and high energy density.
[0059] In some embodiments, the specific surface area of the lithium manganese iron phosphate material is 20-25 m 2 g -1 , in order to obtain higher rate performance.
[0060] In some embodiments, the tap density of the lithium manganese iron phosphate material is 1-1.5 g / cm 3 , to obtain higher energy density.
[0061] According to another aspect of the present invention, there is provided a lithium iron manganese phosphate composite material, comprising the lithium iron manganese phosphate material as described above.
[0062] According to another aspect of the present invention, a positive electrode plate is provided, the positive electrode plate comprising the above lithium iron manganese phosphate material. The lithium iron manganese phosphate material prepared based on the method of the present invention has high stacking density, electrical conductivity and energy density, and has excellent ion transmission rate, rate performance and cycle reversibility, and is a positive electrode material with great application prospects.
[0063] According to another aspect of the present invention, a lithium-ion battery is provided, comprising the positive electrode plate as above, so as to obtain a lithium-ion battery with high capacity, high energy, high-speed charge and discharge performance, good safety, long life and low cost.
[0064] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0065] Example 1
[0066] A lithium manganese iron phosphate material, the preparation method comprising the following steps:
[0067] Step 1: MnCO3, Fe(CH3COO)2·4H2O and H3PO4 are mixed, dispersed with deionized water, and then ball-milled at a speed of 400 rpm for 5 hours using a high-speed planetary ball mill to obtain a first mixed slurry;
[0068] Step 2: Add Li2CO3, pyrophosphate and sucrose to the first mixed slurry, and ball-mill again at a rotation speed of 400 rpm for 5 hours to form a highly stable second mixed slurry.
[0069] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure. During the spray-drying process, the frequency of the feed peristaltic pump is 15 Hz and the temperature is 101°C.
[0070] Step 4: The prepared microsphere structure composite precursor is heated to 650°C at a heating rate of 5°C / min in a N2 atmosphere and calcined for 6 hours to prepare lithium manganese iron phosphate material LiMn 0.8 Fe 0.2 PO4.
[0071] Among them, the molar ratio of Mn element in MnCO3, Fe element in Fe(CH3COO)2·4H2O, phosphorus element in H3PO4 and Li element in Li2CO3 is 0.8:0.2:1:1; taking the sum of the weights of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose as 100%, the mass of pyrophosphate is 1%, the mass of sucrose is 5%, and the mass of water is 100%.
[0072] Example 2
[0073] A lithium manganese iron phosphate material, the preparation method comprising the following steps:
[0074] Step 1: Mix manganese acetate, ferrous oxalate and ammonium dihydrogen phosphate, disperse them with deionized water, and then use a high-speed planetary ball mill to mill them at a rotation speed of 350 rpm for 5 hours to obtain a first mixed slurry;
[0075] Step 2: Add lithium acetate, pyrophosphate and sucrose to the first mixed slurry, and ball-mill again at a rotation speed of 350 rpm for 5 hours to form a highly stable second mixed slurry.
[0076] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure. During the spray-drying process, the flow rate is 20 Hz, the frequency of the feed peristaltic pump is 105°C.
[0077] Step 4: The prepared microsphere structure composite precursor is heated to 580°C at a heating rate of 3°C / min in a N2 atmosphere and calcined for 5 hours to prepare lithium manganese iron phosphate material LiMn 0.5 Fe 0.5PO4.
[0078] Among them, the molar ratio of Mn element in manganese acetate, Fe element in ferrous oxalate, phosphorus element in diammonium phosphate and Li element in lithium acetate is 0.5:0.5:1:1.1; taking the sum of the weights of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose as 100%, the mass of pyrophosphate is 0.5%, the mass of sucrose is 3%, and the mass of water is 80%.
[0079] Example 3
[0080] A lithium manganese iron phosphate material, the preparation method comprising the following steps:
[0081] Step 1: Mix manganese tetraoxide, iron oxide and ammonium phosphate, disperse them with deionized water, and then use a high-speed planetary ball mill to mill them at a speed of 450 rpm for 5 hours to obtain a first mixed slurry;
[0082] Step 2: Add lithium formate, pyrophosphate and sucrose to the first mixed slurry, and ball-mill again at a rotation speed of 450 rpm for 5 hours to form a highly stable second mixed slurry.
[0083] Step 3: spray-dry the second mixed slurry to form a composite precursor with a microsphere structure; during the spray-drying process, the frequency of the feed peristaltic pump is 12 Hz and the temperature is 102°C.
[0084] Step 4: The prepared microsphere structure composite precursor is heated to 620°C at a heating rate of 7°C / min in a N2 atmosphere and calcined for 8 hours to prepare lithium manganese iron phosphate material LiMn 0.6 Fe 0.4 PO4.
[0085] Among them, the molar ratio of the added Mn element in manganese tetraoxide, the Fe element in iron oxide, the phosphorus element in ammonium phosphate and the Li element in lithium formate is 0.6:0.4:1:0.9; taking the sum of the weights of the manganese source, the iron source, the phosphorus source, the lithium source, pyrophosphate and sucrose as 100%, the mass of the pyrophosphate is 2%, the mass of the sucrose is 7%, and the mass of water is 120%.
[0086] Example 4
[0087] The only difference between it and Example 1 is that the calcination temperature is 560° C., as follows:
[0088] A lithium manganese iron phosphate material, the preparation method comprising the following steps: (1) mixing MnCO3, Fe(CH3COO)2·4H2O and H3PO4, dispersing with deionized water, and then using a high-speed planetary ball mill to ball mill for 5 hours at a rotation speed of 400 rpm to obtain a first mixed slurry;
[0089] Step 2: Add Li2CO3, pyrophosphate and sucrose to the first mixed slurry, and ball-mill again at a rotation speed of 400 rpm for 5 hours to form a highly stable second mixed slurry.
[0090] Step 3: The second mixed slurry is spray-dried to form a composite precursor with a microsphere structure. During the spray-drying process, the frequency of the feed peristaltic pump is 15 Hz and the temperature is 101°C.
[0091] Step 4: The prepared microsphere structure composite precursor is heated to 560°C at a heating rate of 5°C / min in a N2 atmosphere and calcined for 6 hours to prepare lithium manganese iron phosphate material LiMn 0.8 Fe 0.2 PO4.
[0092] Among them, the molar ratio of Mn element in MnCO3, Fe element in Fe(CH3COO)2·4H2O, phosphorus element in H3PO4 and Li element in Li2CO3 is 0.8:0.2:1:1; taking the sum of the weights of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose as 100%, the mass of pyrophosphate is 1%, the mass of sucrose is 5%, and the mass of water is 100%.
[0093] Example 5
[0094] The only difference from Example 1 is that the heating rate in step 4 is 10° C. / min.
[0095] Comparative Example 1
[0096] The only difference between it and Example 1 is that sucrose is replaced by starch in step 2.
[0097] Comparative Example 2
[0098] The only difference from Example 1 is that the calcination temperature in step 4 is 500°C.
[0099] Comparative Example 3
[0100] The only difference from Example 1 is that the calcination temperature in step 4 is 720°C.
[0101] Comparative Example 4
[0102] A lithium manganese iron phosphate material, the preparation method comprising the following steps:
[0103] Step 1: MnCO3, Fe(CH3COO)2·4H2O, H3PO4, Li2CO3, pyrophosphate, sucrose and water are mixed in the same amount as in Example 1, and then milled in a high-speed planetary ball mill at a rotation speed of 400 rpm for 10 hours to obtain a mixed slurry.
[0104] Step 2: spray-dry the mixed slurry to form a composite precursor. During the spray-drying process, the feed peristaltic pump frequency is 15 Hz and the temperature is 101°C.
[0105] Step 3: Heat the prepared composite precursor to 650°C at a heating rate of 5°C / min in a N2 atmosphere and calcine for 6 hours to obtain lithium iron manganese phosphate material. 0.8 Fe 0.2 PO4.
[0106] Among them, the molar ratio of Mn element in MnCO3, Fe element in Fe(CH3COO)2·4H2O, phosphorus element in H3PO4 and Li element in Li2CO3 is 0.8:0.2:1:1; taking the sum of the weights of manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose as 100%, the mass of pyrophosphate is 1%, the mass of sucrose is 5%, and the mass of water is 100%.
[0107] Comparative Example 5
[0108] The only difference between this method and Example 1 is that pyrophosphoric acid is not added in step 2.
[0109] Structural characterization and performance testing
[0110] 1. XRD Characterization
[0111] The XRD measurement of lithium iron manganese phosphate material was carried out using a Bruker D8 Discovery X-ray diffractometer. The measurement conditions were: using CuKα radiation and the data collection range was 10° to 80°. 0.8 Fe 0.2 The XRD characterization results of PO4 are as follows Figure 1 As shown, the diffraction pattern is in good agreement with the data of JCPDS No.13-0336, indicating that the prepared LiMn 0.8 Fe 0.2 PO4 is an orthorhombic compound with an ordered olivine structure (space group Pnma); no peaks of impurity phase and amorphous structure of carbon were observed, indicating the high purity lithium manganese iron phosphate phase and low carbon content of the prepared lithium manganese iron phosphate material; the parameters of lithium manganese iron phosphate were calculated by Rietveld refinement using TOPAS 5 software, and the unit cell parameters of lithium manganese iron phosphate were obtained. It is consistent with the results of lithium manganese iron phosphate reported in the literature and has relatively small Rw (6.9%) and Rp (5.4%) factors, indicating a good fitting result.
[0112] 2. Scanning electron microscopy (SEM) characterization and high-resolution transmission electron microscopy (HRTEM) characterization
[0113] The morphology of lithium manganese iron phosphate material was characterized using a scanning electron microscope (SEM, JEOL JSM-6390). 0.8 Fe 0.2 The SEM characterization results of PO4 are as follows Figure 2 shown. Figure 2 Figure (a) clearly shows the prepared LiMn 0.8 Fe 0.2 PO4 material has a distinct spherical morphology, and the size of the micron-sized secondary particles is distributed in the range of 10-20 microns. As can be seen from the enlarged single micron-sized secondary particle in Figure (b), the secondary particles are formed by the accumulation of relatively small nano-sized primary particles, and the size of the primary particles is about 50-100nm. LiFe 0.2 Mn 0.8 PO4 particles can have a higher bulk density.
[0114] In order to investigate the element distribution in micrometer-sized secondary particles, energy dispersive X-ray (EDX) elemental imaging of Mn, Fe, P, and O was performed, e.g. Figure 2 As shown in Figure (c), the distribution of Mn and Fe is consistent with the distribution of P and O elements, which indicates that the transition metals are uniformly distributed in the microspheres.
[0115] The HRTEM morphology of the lithium manganese iron phosphate material prepared in Example 1 was characterized using a transmission electron microscope (JEOL JEM-2010). Figure 3 As shown, it can be seen that the surface of the lithium manganese iron phosphate nanoparticles is tightly wrapped by a continuous carbon layer of about 3 nanometers thick.
[0116] Combined with SEM characterization and HRTEM characterization, it can be known that the lithium manganese iron phosphate material prepared in Example 1 has a porous microsphere structure, and the porous microspheres are formed by the aggregation of nano-primary particles coated with a continuous carbon layer on the surface. The particle size of the porous microspheres is 10-20 microns, the shape is regular, the thickness of the conductive carbon layer is about 3nm, and the porous microsphere particles have interconnected three-dimensional pore channels.
[0117] 3. Specific surface area characterization
[0118] The specific surface area of the lithium manganese iron phosphate materials prepared in the embodiment and the comparative example was tested using the Brunauer–Emmett–Teller (BET) method with a specific surface area and pore size analyzer (Quadasorb SI Automated Surface Area and Pore Size Analyzer). The results are shown in Table 1.
[0119] 4. Test of powder resistivity
[0120] The powder resistivity of the lithium iron manganese phosphate materials obtained in the embodiment and the comparative example was tested using a four-probe instrument. The test results are shown in Table 1.
[0121] 5. Tap density test
[0122] The tap density of the lithium manganese iron phosphate material obtained in the embodiment and the comparative example was tested using a tap density meter (U.S. Quantachrome, DAT-6-220). The specific steps are as follows: the sample is placed in a measuring cylinder and vibrated 3000 times, the volume of the measuring cylinder after vibration is read and the tap density is calculated. The results are shown in Table 1.
[0123] 6. Electrochemical test
[0124] Lithium-ion battery preparation, the specific steps are as follows:
[0125] Preparation of positive electrode sheet: based on the mass of positive electrode material, conductive agent and polyvinylidene difluoride (PVDF) adhesive as 100%, 90% of positive electrode material, 5% of conductive agent and 5% of PVDF adhesive are dispersed in 1-methyl-2-pyrrolidone (NMP), and then evenly applied on aluminum foil; the applied aluminum foil is dried at 80°C for 60 minutes, and then vacuum dried at 100°C for 12 hours; the dried aluminum foil is cut into discs with a diameter of 12 mm to obtain positive electrode sheets, and the loading amount of lithium manganese iron phosphate material on the positive electrode sheet is about 5 mg / cm 2 .
[0126] Battery assembly: A standard CR2016 button mold was used for battery assembly. The battery assembly was carried out in a glove box filled with argon. Lithium metal was used as the negative electrode of the standard half-cell, and the prepared positive electrode sheet was used as the positive electrode. LiPF6 was dissolved in a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and methyl acetate (EMC) (the volume ratio of EC, DMC and EMC was 1:1:1) to prepare an electrolyte of 1 mol L -1 LiPF6 solution.
[0127] According to the above method, the lithium manganese iron phosphate materials prepared in the embodiment and the comparative example were used as positive electrode materials to prepare lithium ion batteries for charge and discharge tests and cycle performance tests at room temperature, as follows:
[0128] (1) Charge and discharge test: The charge and discharge specific capacity of the lithium-ion battery was tested at 0.2C, 1C, 2C and 5C rates at 25°C in the voltage range of 2.0-4.5V. The 0.2C charge specific capacity, 0.2C discharge specific capacity, 0.2C first cycle coulomb efficiency, 1C charge specific capacity, 2C charge specific capacity and 5C charge specific capacity at 25°C are shown in Table 1.
[0129] (2) Cyclic performance test at room temperature: 200 cycles of testing were performed at 25°C, 1C rate and 2.0-4.5V voltage range. The capacity retention rate after 200 cycles at 1C at 25°C is shown in Table 1.
[0130] Then the charge and discharge test, cycle performance test at room temperature, cycle performance test at high temperature and rate performance test are carried out.
[0131] Table 1
[0132]
[0133] It can be seen from the data in Table 1 that, compared with Comparative Examples 1 to 5, the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of Examples 1 to 5 of the present invention has a higher tap density, a smaller powder resistivity, a higher charge and discharge specific capacity and a higher first-cycle coulomb efficiency, and a better rate performance.
[0134] From the comparison between Example 1 and Comparative Example 1, it can be seen that compared with the use of high molecular weight organic starch as the carbon source of the carbon coating layer in Comparative Example 1, the use of small molecular weight sucrose as the carbon source of the carbon coating layer in Example 1 is that it is easier to form a uniform and continuous carbon layer on the lithium manganese iron phosphate nanoparticles during the pyrolysis process, the powder resistivity is significantly reduced, and the discharge specific capacity at 0.2C, 1C, 2C and 5C is also relatively high. The capacity retention rate results of Example 1 and Comparative Example 1 at 1C for 200 cycles are as follows: Figure 4 As shown, the carbon source in Example 1 provides better cycle stability, and the discharge capacity can still be maintained at 97.16% after 200 cycles, while that in Comparative Example 1 is only 87.04%.
[0135] By comparing Example 1, Example 4 and Comparative Example 2, it can be seen that compared with the lower calcination temperature used in Comparative Example 2, the powder resistivity of the lithium iron manganese phosphate material in Example 1 and Example 4 is significantly reduced, the specific surface area, charge and discharge specific capacity, battery efficiency and capacity retention rate are significantly improved, and the tap density is also higher. By comparing Example 1 and Comparative Example 3, it can be seen that compared with the higher calcination temperature used in Comparative Example 3, the powder resistivity of the lithium iron manganese phosphate material in Example 1 is significantly reduced, and the charge and discharge specific capacity, battery efficiency and capacity retention rate are significantly improved. At the calcination temperature (520-700°C) in the present application, especially at 580-650°C, it is easier to generate a uniformly connected conductive carbon layer and a regular porous microsphere structure, which is beneficial to improve the conductive properties of the lithium iron manganese phosphate material.
[0136] By comparing Example 1 and Comparative Example 4, it can be seen that under the same conditions of raw materials and calcination process, compared with the direct ball milling of each raw material to prepare the slurry in Comparative Example 4, the slurry is prepared by step-by-step dispersion in Example 1, and the powder resistivity and electrochemical properties of the prepared lithium manganese iron phosphate are far superior to those in Comparative Example 4.
[0137] By comparing Example 1 and Comparative Example 5, it can be seen that under the same mixing method and calcination process conditions, compared with Comparative Example 5 in which no pyrophosphoric acid is added, the powder resistivity of the lithium manganese iron phosphate prepared in Example 1 is much smaller than that in Comparative Example 5, and the addition of pyrophosphoric acid can promote the pyrolysis of the carbon source to form a uniform and continuous carbon coating layer, and the charge and discharge specific capacity and tap density of Example 1 are also much higher than those of Comparative Example 5. The addition of pyrophosphoric acid is conducive to the formation of a uniform and regular porous microsphere structure and a carbon coating layer, which is conducive to improving the electrochemical properties and tap density of the composite lithium manganese iron phosphate positive electrode material.
[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing lithium manganese iron phosphate material, characterized in that: The steps include: Step S1, mixing a manganese source, an iron source, a phosphorus source and water by ball milling to obtain a first mixed slurry; Step S2, ball-milling the lithium source, pyrophosphate, sucrose and the first mixed slurry to obtain a second mixed slurry; Step S3, spray drying the second mixed slurry to obtain a composite precursor with a microsphere structure; Step S4, calcining the composite precursor of the microsphere structure at a calcination temperature of 520-700° C. in an inert gas atmosphere to obtain a lithium manganese iron phosphate material.
2. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The molar ratio of the manganese element in the manganese source, the iron element in the iron source, the phosphorus element in the phosphorus source and the lithium element in the lithium source is (0.5-0.8): (0.2-0.5): 1: (0.8-1.2), preferably (0.5-0.8): (0.2-0.5): 1: (0.9-1.1); and / or, Based on the sum of the weight of the manganese source, the iron source, the phosphorus source, the lithium source, the pyrophosphate and the sucrose being 100%, the mass of the sucrose is 3%-7%; and / or, The mass of the pyrophosphoric acid is 0.5%-2% based on the sum of the weights of the manganese source, the iron source, the phosphorus source, the lithium source, the pyrophosphoric acid and the sucrose as 100%; Taking the sum of the weights of the manganese source, iron source, phosphorus source, lithium source, pyrophosphate and sucrose as 100%, the mass of the water is 80% to 300%, and preferably the mass of the water is 90% to 120%.
3. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: The manganese source is selected from one or more of manganese carbonate, manganese acetate, manganese phosphate, manganese oxalate, manganese hydroxide, manganese nitrate, manganese tetraoxide, manganese trioxide or manganese dioxide; and / or, The iron source is selected from one or more of ferrous acetate, ferrous oxalate, ferrous chloride, ferrous nitrate, ferrous oxide, ferrous sulfate, ferric chloride, ferric nitrate, ferric sulfate, ferric oxide, ferric oxide, ferric phosphate or ferrous phosphate; The phosphorus source is selected from one or more of phosphoric acid, ammonium dihydrogen phosphate, ammonium phosphate, phosphorus pentoxide, phosphorous acid, and diammonium hydrogen phosphate; and / or, The lithium source is selected from one or more of lithium carbonate, lithium bicarbonate, lithium acetate, lithium formate, lithium citrate, lithium chloride, lithium bromide, lithium hydroxide, lithium tert-butoxide, lithium benzoate, lithium phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, lithium oxalate or lithium sulfate.
4. The method for preparing lithium iron manganese phosphate material according to claim 1, characterized in that: In step S4, the calcination time is 4-8 hours, preferably 6 hours; Preferably, in step S4, the calcination temperature is 580-650°C; Preferably, in the step S4, the composite precursor of the microsphere structure is heated to a calcination temperature at a heating rate of 3-7° C. / min under an inert gas atmosphere.
5. The method for preparing the lithium iron manganese phosphate material according to any one of claims 1 to 4, characterized in that: In the step S1, a manganese source, an iron source and a phosphorus source are first mixed to obtain a mixture, and the mixture is dispersed with deionized water before being ball milled; Preferably, in step S1, the ball milling time is 350-450 rpm, and the ball milling time is 2-8 h; Preferably, in step S2, the ball milling time is 350-450 rpm, and the ball milling time is 2-8 h; Preferably, in the spray drying process, the frequency of the feed peristaltic pump is 5-40 Hz and the temperature is 100-110°C.
6. A lithium manganese iron phosphate material, characterized in that: The lithium iron phosphate material is prepared according to the preparation method of any one of claims 1-5, wherein the lithium iron phosphate material has a porous microsphere structure, and the porous microsphere is formed by aggregation of nano primary particles, and the nano primary particles include lithium iron phosphate nanoparticles and a carbon layer coated on the surface of the lithium iron phosphate nanoparticles.
7. The lithium iron manganese phosphate material according to claim 6, characterized in that: The particle size of the porous microspheres is 10-20 microns; and / or, The particle size of the nano primary particles is 50-100 nm; and / or, The thickness of the carbon layer is 2-5 nm; and / or, The material composition formula of the lithium manganese iron phosphate nanoparticles is LiMn 1-x Fe x PO4, wherein 0.2≤x≤0.5; and / or The specific surface area of the lithium manganese iron phosphate material is 20-25m 2 g -1 and / or, The tap density of the lithium manganese iron phosphate material is 1-1.5 g / cm 3 .
8. A lithium manganese iron phosphate composite material, characterized in that: Contains the lithium manganese iron phosphate material as described in claim 6 or 7.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium manganese iron phosphate material as described in claim 6 or 7.
10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparation method of lithium iron phosphate composite material modified by lithium pyrophosphate
CN102244241A
Lithium ion battery composite positive electrode material and preparation method
CN112635722A
Lithium manganese iron phosphate composite material, preparation method thereof and battery
CN115806281A
Precursor coated and modified by borophosphate and pyrophosphate as well as preparation method and application of precursor
CN116588992A
Preparation method of high-compaction type co-doped lithium iron phosphate material
CN118811788A
Cited By
Positive electrode material and preparation method and application thereof
CN120767327A
Lithium manganese iron phosphate material, preparation method therefor, and use thereof
WO2026123660A1